2010
DOI: 10.14430/arctic424
|View full text |Cite
|
Sign up to set email alerts
|

Protecting the Health of First Nation Personnel at Contaminated Sites: A Case Study of Mid-Canada Radar Line Site 050 in Northern Canada

Abstract: Recently, First Nation (FN) organizations have entered into agreements with federal and provincial government representatives to remediate radar-line sites in Ontario. These agreements stipulated that FN people would take part in the site delineation and remediation process to gain job experience and economic benefits. One important aspect of the process was protecting FN personnel from contaminant exposure and thus, from potential negative health outcomes associated with the cleanup work itself. In this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Traditional food systems are also highly influenced by resource availability and the physical environment (Kuhnlein et al, 2001;Waldram, 1985;Wein, Henderson Sabry, & Evers, 1991). Previous studies examining traditional food access and availability have often taken place in remote regions where environmental safety issues associated with traditional foods such as wild meats and fish have been viewed with concern, particularly in northern communities where contaminants have accumulated up the food chain in many species (Furgal & Seguin, 2006;Kuhnlein & Chan, 2000;Receveur et al, 1997;Tsuji et al, 2005;Waldram, 1985;Wein et al, 1991). Comparatively, in southern Canada, few studies have reported on environmentally contaminated locally harvested foods (Abonyi, 2001;Bruyere & Garro, 2000;Chan, Trifonopoulos, Ing, Receveur, & Johnson, 1999;Garro, 1994;Lang, 1989), or their decreased access due to environmental modification, such as urban development and the displacement of Indigenous species (Doolan, 1991;Hlimi, Skinner, Hanning, Martin, & Tsuji, 2012;O'Neil, Reading, & Leader, 1998;Turner & Turner, 2008;Wheatley & Paradis, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Traditional food systems are also highly influenced by resource availability and the physical environment (Kuhnlein et al, 2001;Waldram, 1985;Wein, Henderson Sabry, & Evers, 1991). Previous studies examining traditional food access and availability have often taken place in remote regions where environmental safety issues associated with traditional foods such as wild meats and fish have been viewed with concern, particularly in northern communities where contaminants have accumulated up the food chain in many species (Furgal & Seguin, 2006;Kuhnlein & Chan, 2000;Receveur et al, 1997;Tsuji et al, 2005;Waldram, 1985;Wein et al, 1991). Comparatively, in southern Canada, few studies have reported on environmentally contaminated locally harvested foods (Abonyi, 2001;Bruyere & Garro, 2000;Chan, Trifonopoulos, Ing, Receveur, & Johnson, 1999;Garro, 1994;Lang, 1989), or their decreased access due to environmental modification, such as urban development and the displacement of Indigenous species (Doolan, 1991;Hlimi, Skinner, Hanning, Martin, & Tsuji, 2012;O'Neil, Reading, & Leader, 1998;Turner & Turner, 2008;Wheatley & Paradis, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Health Issues: Health Canada became involved in assessing the Fort Albany FN workers' contaminant body burdens only after they had worked in the contaminated area; body burdens prior to work in the contaminated area were not measured (Tsuji et al, 2005). The Band generally felt that Health Canada did not seek Band or community input.…”
Section: Implementing the Essential Elements Of The Memorandum Of Undmentioning
confidence: 99%
“…A study on risk mapping of contaminants on the lands of the Navajo Nation (Churchrock Chapter, New Mexico) and a survey of 151 community members found that the maps were helpful in avoiding the risk of consumption of contaminated food and water arising from the Churchrock Uranium Mine Site (deLemos et al, 2009). Another study cited the effectiveness of safety protocols (education on the proper handling of hazardous wastes) for nine Fort Albany Cree First Nation workers (Ontario) employed to clean-up the Mid-Canada Radar Contaminated site, finding no significant burden of blood lead and PCBs before and after the clean-up (Tsuji et al, 2005). Three studies explored the influence of a lay-health advisor intervention on blood lead concentrations in children living in proximity to the Tar Creek Superfund Site, comparing results between members of the Eight Tribes and Nations of Northeastern Oklahoma and Non-Indigenous, white participants that lived near the site.…”
Section: Resultsmentioning
confidence: 99%
“…Literature on traditional food systems across Canada and the US evidences a diversity of exposure pathways unique to Indigenous communities, including for example through subsistence diets that include wild foods and medicinal plants (Chan, Fediuk, et al, 2021; Fernández-Llamazares et al, 2020; Jonasson et al, 2019). Notably, while peer-reviewed literature examined in this review documents the presence of a variety of contaminants in plant foods, wildlife, wild game, and human biomarkers (Brown et al, 2014; Denham et al, 2005; Fitzgerald et al, 1996; Fitzgerald et al, 2004; Flett et al, 2021; Garvin, 2018; Goncharov et al, 2008; Kegler & Malcoe, 2004; Michelle C Kegler et al, 2010; Koch et al, 2013; Rock et al, 2019; Samuel-Nakamura et al, 2017; Sarkar et al, 2019; Tsuji et al, 2005), information on these potential exposure sources is not captured in federal databases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation